Gross morphometric and histological effect of turmeric and vitamin C on alcohol induced liver toxicity among albino rats - Lwunza, Libamila Hans; Rodrick, Mwachi Sikhama; Allan, Khisa Wanjala (International Journal of Research in Medical Sciences, 2025)
Background: Turmeric has curcumin, as active constituent that improves ethanol-induced hepatotoxicity, prevents accumulation of Reactive Oxygen Species (ROS) and suppression of systems of anti-oxidation in the liver. Methods: A total of 25 albino rats of species Rattus Norvegicus were simpled randomly picked and grouped into five groups. They were exposed to alcohol, turmeric and Vitamin C at calculated doses. Thereafter, the animals were sacrificed, hepatotoxicity was confirmed and histological study was conducted. Results: Negative control group (food and water ad-libitum), where the central vein, hepatocytes, hepatic triad and capillary sinusoid appeared normal as shown in Figure 1a. Group 2 (alcohol 3g/kgbwt) that showed the Sinusoids had marked dilatation and the central vein had also dilated and congested, Focal points of hemorrhagic necrosis were observed and patches of macrovascular steatosis were observed shown in Figure 1b. Liver sections from Group III (alcohol 3 g/kgbwt and turmeric 0.187 mg/kg/day) showed the central vein was slightly dilated as compared to control and smaller to group that only received alcohol. Sections from group IV (alcohol 3 g/kgbwt and vitamin C 0.3 mg/kg/day) showed the central vein was slightly dilated and not congested as compared to the alcohol only group. The sinusoids and the hepatocytes were normal shown in Figure 2b. Sections from group V (alcohol 3 g/kgbwt and vitamin C 0.3 mg/kg/day and turmeric 0.187mg/kg/day) the central vein, sinusoids and hepatocytes had almost similar histological characteristics as the negative control group (Group 1) as shown in Figure 2c. Conclusions: Turmeric and vitamin C have histomorphological protective effects on alcohol induced liver toxicity among albino rats.